The Correlation Between Preconception Body Mass Index And Upper Arm Circumference With The Incidence Of Anemia In Third-Trimester Pregnant Women In The Working Area Of Waru Public Health Center - Erinda Puteri, Abrillah Giosika; Lini Anisfatus Sholihah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Anemia during pregnancy is a condition in which the body of pregnant woman experiences reduction in hemoglobin levels due to iron deficiency during pregnancy period, potentially causing complications. This research aims to determine the relationship between preconception body mass index (BMI) and upper arm circumference (UAC) with the occurrence of anemia in third-trimester pregnant women in the Waru Public Health Center working area. The method employed is quantitative analytic observational, using cross-sectional study design, and using secondary data taken from maternal antenatal care (ANC) records. Respondents were 94 third trimester pregnant women selected through simple random sampling technique. Data were analyzed using the chi-square test and calculation of the odds ratio (OR). The results indicated a prevalence of 53.2% for anemia occurring in third-trimester pregnant women in the Waru Public Health Center. Analysis using chi-square obtained p-value = 0.045 and OR = 2.329 for preconception body mass index (BMI) with the occurrence of anemia in third-trimester pregnancy, p-value = 0.276 and OR = 2.864 for preconception upper arm circumference (UAC) with the occurrence of anemia in third-trimester pregnancy. These results showed that there is a association between preconception body mass index (BMI) and the occurrence of anemia in third-trimester pregnancy, while there is no association between preconception upper arm circumference (UAC) and the occurrence of anemia in third-trimester pregnancy. It is expected that women of reproductive age who are preparing for pregnancy will maintain a normal nutritional status during the preconception period to prevent pregnancy anemia as an early intervention.